2021
DOI: 10.1108/heed-01-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the efficacy of English proficiency on initial semestral results for higher education L1 English speakers in a multilingual context

Abstract: PurposeThe purpose of this paper is to evaluate an English Proficiency (EP) programme and its efficacy with respect to students' academic performance in a university within a multi-lingual context, as the programme had been in effect for some years.Design/methodology/approachA quasi-experimental approach was used to study the efficacy of an EP programme in a university within a multilingual context. Data across two academic years were used, along with regression discontinuity design.FindingsResults suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is expected that with enhanced EAP skills, students would be more confident and better supported in their academic pursuits. This expectation is not unfounded, as a separate study found that students who completed the same EAP programme in the university had better than predicted GPA [ 21 ], suggesting that English proficiency has a positive impact on GPA. In this study, 24 of 50 students interviewed articulated that completing and passing the EAP programme helped with improving their English proficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected that with enhanced EAP skills, students would be more confident and better supported in their academic pursuits. This expectation is not unfounded, as a separate study found that students who completed the same EAP programme in the university had better than predicted GPA [ 21 ], suggesting that English proficiency has a positive impact on GPA. In this study, 24 of 50 students interviewed articulated that completing and passing the EAP programme helped with improving their English proficiency.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that, based on the university in this study, an earlier quasi-experimental study found that EAP provisions had a statistically significant and positive intervention effect on the GPA of the first semester upon matriculation [ 21 ]. This earlier study provided information limited to intervention effects on GPA and hence, it is worth exploring students’ perceptions and learning experiences of EAP programmes in this study.…”
Section: Literature Reviewmentioning
confidence: 99%